UMPSA strengthens collaboration with PTPTN - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 27 August 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) has further strengthened its collaboration with the National Higher Education Fund Corporation (PTPTN) by signing a memorandum of understanding (MoU) today.